The Influence of Transformational Leadership on Employee Performance in The Salapian District Office, Langkat District - Sugiono, Sugiono; B, Mesra (PT. Multidisciplinary Press Indonesia, 2024)
The purpose of this research is to determine and analyze the influence of transformational leadership on employee performance at the Salapian District Head Office. This research was conducted using a causal associative quantitative approach. The sample used was all company employees, with a total of 50 people. The research results show that transformational leadership has a positive and significant effect on employee performance. This is shown by the T-count value of 3.193 which is greater than the T-table of 1.67722, as well as the P-Value value of 0.002 which is smaller than 0.05. The regression coefficient shows that if transformational leadership is increased by 1 unit, employee performance will increase by 1,319 units assuming other variables remain constant. Apart from that, the results of the determination test show an Adjusted R Square value of 0.150 or 15.00%, which indicates that transformational leadership has a low influence on employee performance, while the remaining 75.00% is influenced by other factors that have not been studied. Thus, partially, transformational leadership has a positive and significant effect on employee performance at the Salapian Subdistrict Office, Langkat Regency. This identifies that, meaning, improvements in transformational leadership can contribute to improving employee performance.